Investigating the requirement of Clrn2 for mammalian hearing - Dunbar, LA (2021)
Cochlear inner and outer hair cells are the functional units of mammalian hearing. At their apex, specialised microvilli known as stereocilia are arranged in three rows of ascending height, and the mechano-electrical transduction (MET) channels, crucial for converting sound-induced fluid waves into electrical signals, reside at the top of the two shorter rows. Each MET channel is tethered to the adjacent stereocilia in a taller row via a tip link, which mechanically gates the channel upon deflection of the stereocilia bundle. The genetic mechanisms involved in the development and maintenance of the hair bundle are poorly understood.